Identification of Fibrinogen Derivatives in Plasma Samples - Graeff, H; von Hugo, R (Thrombosis and Haemostasis, 1972)
The observation of fibrinogen derivatives with a molecular weight higher than the parent molecule in human cases of DIC initiated the present methodological study. These derivatives were identified by the following methods : 2.5 M β-alanine precipitation of the plasma samples, PAA gel electrophoresis, intra gel immunoprecipitation and agarose gel chromatography. In the plasma of a patient with severe eclampsia and laboratory signs of DIC two derivatives with a molecular weight higher than that of fibrinogen were identified according to their relative electrophoretic mobilities: 0.18 and 0.28 × 10−5 cm2/V × sec (fibrinogen: 0.43 × 10−5 cm2/V × sec). Electrophoretic studies in the presence of 5 M urea indicated that the 0.28 derivative is a complex probably formed by fibrinogen and a fibrin monomer.